Neodymium isotopes in authigenic phases, bottom waters and detrital sediments in the Gulf of Alaska and their implications for paleo-circulation reconstruction. (15th November 2016) - Du, Jianghui; Haley, Brian A.; Mix, Alan C.
Abstract: The isotopic composition of neodymium ( ε Nd ) extracted from sedimentary Fe–Mn oxyhydroxide offers potential for reconstructing paleo-circulation, but its application depends on extraction methodology and the mechanisms that relate authigenic ε Nd to bottom water. Here we test methods to extract authigenic ε Nd from Gulf of Alaska (GOA) sediments and assess sources of leachate Nd, including potential contamination from trace dispersed volcanic ash. We show that one dominant phase is extracted via leaching of core-top sediments. Major and trace element geochemistry demonstrate that this phase is authigenic Fe–Mn oxyhydroxide. Contamination of leachate (authigenic) Nd from detrital sources is insignificant (<1%); our empirical results are consistent with established kinetic mineral dissolution rates and theory. Contamination of extracted ε Nd from leaching of volcanic ash is below analytical uncertainty. However, the ε Nd of core-top leachates in the GOA is consistently more radiogenic than bottom water. We infer that authigenic phases record pore water ε Nd, and the relationships of ε Nd among bottom waters, pore waters, authigenic phases and detrital sediments are primarily governed by the exposure time of bottom water to sea-floor sediments, rate of exchange across the sediment-water interface and the reactivity and composition of detrital sediments. We show that this conceptual model is applicable on the Pacific basin scale and provide a new framework to understand the role of authigenic phases in both modern and paleo-applications, including the use of authigenic ε Nd as a paleo-circulation tracer.